Assessment of Fertilizer Blended Waste on Soil and Water at Fertilizer Blending Company in Bokkos, Plateau State, Nigeria. - Ezikiel , Trengshak Geoffrey; Karniliyus Emmanuel Daring; Ishaq Shaibu Eneji (International Journal of Natural Sciences: Current and Future Research Trends, 2020)
The volume of waste generated from fertilizer blending company in Bokkos call for concerned due to environmental and human risk. Therefore assessing the concentration of soil and water parameters forms the basis for this research. Soil and water samples were collected within the vicinity of the company and analysed using standard techniques. The results obtained, for water samples in mg/L showed; pH (8.3±0.1), EC (226±28?S/cm ), TSS (0.50±0.2), free chloride (0.04±0.04), PO43- (2.1±1.0), SO4 2-(1.7±3.0), NO3- (19.1±3.0), Hardness (43.3±6.4), P (0.70±0.3), P2O5 (1.5±0.8). The results for soil samples in mg/L, showed; pH in water (6.84±0.1), EC (204±54.1?S/cm), OC (0.80±0.2), OM (1.4±0.3), N (28.7±9.3), P (2.11±0.3), CEC (7.07±0.3), K (1.77±0.84) and moisture content of (9.07±0.14%). The results statistically correlate at 95% confidence level. This study has revealed that the water and soil within the environs of the company is ideal for human consumption and agricultural purpose. However, sustained monitoring of heavy metals in the environs of the company is hereby recommended to avert environmental and human hazard.